Scarabs from excavations in Palestine/Transjordan from Iron Age I, (c. 1200-1000 B.C.) : including a framework for a computerized picture database (ICONBASE) - Eggler, Jurg (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1992.